Factors Affecting Poverty in Central Java Province 2018-2020: Faktor-Faktor Yang Mempengaruhi Kemiskinan di Provinsi Jawa Tengah Tahun 2018-2020 - Muhsin, Fikri Zakaria; Setyowati, Eni (Universitas Muhammadiyah Sidoarjo, 2022)
Poverty is one of the diseases that exist in the economy of each country, especially in Indonesia, which is included in the category of developing countries which can still be said to have a fairly high poverty rate. The problem of poverty is a problem that is so complex and always exists in social life that involves aspects of human life, even though its presence is often not realized by the person concerned. This study aims to analyze the effect of Education, Population, Gross Regional Domestic Product (GRDP) and Labor Force on the level of Poverty in Central Java in 2018-2020. The data obtained is from the website of the Central Statistics Agency (BPS) of Central Java Province. Data were taken from 29 districts and 6 cities in Central Java Province. The analysis tool uses panel data regression. The results of this study indicate that the Fixed Effect Model (FEM) is the selected panel data regression model. Based on the test results, it was found that the level of significance of Education, Population and Gross Regional Domestic Product (GRDP) had an effect on the level of Poverty in Central Java in 2018-2020.